Cerebrospinal fluid findings in patients with seizure in the setting of COVID-19: A review of the literature. (July 2021) - Carroll, Elizabeth; Melmed, Kara R.; Frontera, Jennifer; Placantonakis, Dimitris G.; Galetta, Steven; Balcer, Laura; Lewis, Ariane
Highlights: We identified 69 patients with COVID-19 who had a seizure and CSF obtained. CSF SARS-CoV-2 was positive for 6/45 (13%) patients. Of 11 patients who had CSF autoimmune antibody panels, 2 (18%) were positive. Based on CSF, it is unlikely seizures in these patients are a result of viral neuroinvasion. Abstract: We reviewed the literature on cerebrospinal fluid (CSF) studies in patients who had a seizure in the setting of COVID-19 infection to evaluate for evidence of viral neuroinvasion. We performed a systematic review of Medline and Embase to identify publications that reported one or more patients with COVID-19 who had a seizure and had CSF testing preformed. The search ranged from December 1st 2019 to November 18th 2020. We identified 56 publications which described 69 unique patients who met our inclusion criteria. Of the 54 patients whose past medical history was provided, 2 (4%) had epilepsy and 1 (2%) had a prior seizure in the setting of hyperglycemia, but the remaining 51 (94%) had no history of seizures. Seizure was the initial symptom of COVID-19 for 15 (22%) patients. There were 26 (40%) patients who developed status epilepticus. SARS-CoV-2 PCR testing was performed in the CSF for 45 patients; 6 (13%) had a positive CSF SARS-CoV-2 PCR, only 1 (17%) of whom had status epilepticus. The cycle thresholds were not reported. Evaluation for CSF SARS-CoV-2 antibodies (directly or indirectly, via testing for CSF oligoclonal bands or immunoglobulins) was performed in 26 patients, only 2 (8%) of whom had evidence of intrathecal antibody synthesis. Of the 11 patients who had CSF autoimmune antibody panels tested, 1 had NMDA antibodies and 1 had Caspr-2 antibodies. Detection of SARS-CoV-2 in the CSF of patients with seizures who have COVID-19 is uncommon. Our review suggests that seizures in this patient population are not likely due to direct viral invasion of the brain.